KIR gene content diversity in a Zimbabwean population: does KIR2DL2 have a role in protection against human immunodeficiency virus infection? - Mhandire, K; Zijenah, L; Yindom, L; Duri, K; Mlambo, T; Tshabalala, M; Mazengera, L; Mhandire, D; Musarurwa, C; Dandara, C; Rowland-Jones, S; Matarira, H; et al. (Mary Ann Liebert, 2016)
Killer cell immunoglobulin-like receptors (KIRs) mediate natural killer cell function through interaction with their cognate human leukocyte antigen ligands. Thus, KIR gene variants have been implicated in resistance or susceptibility to viral infections. However, research on the role of these variants remains contradictory and inconclusive. In the present study, we investigated KIR gene content diversity and its association with human immunodeficiency virus (HIV) infection in an adult Black Zimbabwean population. Presence or absence of 15 KIR genes was determined in 189 HIV-infected adults and 97 HIV-uninfected blood donors using sequence specific primer polymerase chain reaction. Frequencies of KIR genes, genotypes, and haplotypes were compared between the cases and controls to identify putative associations between KIR gene variants and HIV status. We report in this study the frequencies of 15 KIR genes and 43 KIR genotypes (40 known and 3 novel) among Zimbabweans. Importantly, the frequency of the inhibitory KIR2DL2 gene was significantly higher in the uninfected group (62%) compared to the HIV-infected group (47%) (OR = 0.55, 95% CI: 0.33-0.90, p = 0.019). KIR2DL2/2DL2 homozygosity was also significantly higher in the uninfected group (35%) compared to HIV-infected group (53%) (OR = 0.33, 95% CI: 0.16-0.72, p = 0.005) under a recessive model. We conclude that the KIR2DL2 gene may be involved in protection against HIV infection. It may be possible that inhibitory KIR genes may have an important role to play in HIV acquisition among populations of African origin in whom the activating KIR genes are less frequent compared to among Caucasians.